2008
DOI: 10.1115/1.3005202
|View full text |Cite
|
Sign up to set email alerts
|

Analogy of Strain Energy Density Based Bone-Remodeling Algorithm and Structural Topology Optimization

Abstract: In bone-remodeling studies, it is believed that the morphology of bone is affected by its internal mechanical loads. From the 1970s, high computing power enabled quantitative studies in the simulation of bone remodeling or bone adaptation. Among them, Huiskes et al. (1987, "Adaptive Bone Remodeling Theory Applied to Prosthetic Design Analysis," J. Biomech. Eng., 20, pp. 1135-1150) proposed a strain energy density based approach to bone remodeling and used the apparent density for the characterization of intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Bone remodeling simulation was also conducted by means of structural topology optimization: Hollister et al (1994) used the homogenization method to obtain the architecture of microtrabecular bone, and Bagge (2000) used topology optimization with compliance minimization to determine the initial material distribution for a femur. Jang et al (2008) studied the analogy between the two seemingly different approaches: strain energy density (SED)-based bone remodeling algorithm and the topology optimization method. They showed that topology optimization and the bone remodeling equations produced equivalent solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Bone remodeling simulation was also conducted by means of structural topology optimization: Hollister et al (1994) used the homogenization method to obtain the architecture of microtrabecular bone, and Bagge (2000) used topology optimization with compliance minimization to determine the initial material distribution for a femur. Jang et al (2008) studied the analogy between the two seemingly different approaches: strain energy density (SED)-based bone remodeling algorithm and the topology optimization method. They showed that topology optimization and the bone remodeling equations produced equivalent solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, we like to clarify and strengthen the connection between models of evolutionary problems such as bone remodeling and damage evolution, on the one hand, and structural optimization formulations, on the other. Such a connection is hinted at in several publications, see, e.g., Achtziger et al [1] and Jang et al [8], but since the dynamical systems concept has been missing, this has not been achieve to a full extend in our view. These issues were further discussed in our previous paper [11].…”
Section: Introductionmentioning
confidence: 75%
“…In fact, when the previous remark holds, (8) is equivalent to the following definition of forces as (generalized) derivative of a potential −R ∈ ∂f e (ρ),…”
Section: The Case Of Constant Forcesmentioning
confidence: 99%
“…For the numerical integration of (13), including (14) as a special case, we discretize time into steps of length ∆t. Given a solution ρ n at time t n , we find the…”
Section: Methodsmentioning
confidence: 99%
“…Research aimed at applying topology optimization theory to bone remodeling can be found in, e.g., recent work by Jang and Kim [11,12,13], while studies with the converse aim, i.e., applying bone remodeling theories in structural and topology optimization, can be found in Penninger et al [19] and Andreaus et al [1]. The theoretical basis for this connection of theories is independently discussed in Jang et al [14] and Klarbring and Torstenfelt [15,16]. To be more specific, in the latter works we showed that there is a one-to-one correspondence between a dynamical systems approach to SIMP topology optimization and the apparent density bone remodeling theory of Harrigan and Hamilton [8,9].…”
Section: Introductionmentioning
confidence: 99%